The Term Structure of Interest Rates: A Cointegration Analysis in the Non-Linear STAR Framework - GÜNEY, Pelin ÖGE (Journal of Economics and Behavioral Studies, 2013)
This paper analysis the term structure of interest rates for the Group of Seven (G7) countries. In addition to standard cointegration testing procedures, a cointegration test in a nonlinear smooth transition autoregression (STAR) framework developed by Kapetanios et al. (2006) is also employed. While the standard cointegration test results suggest the existence of cointegration relationship between short and long-term interest rates for Canada, France, Italy, Japan, and US data, these tests fail to establish a cointegration relationship for Germany and the United Kingdom. In case we take account of cointegration with non-linear adjustment, the results provide clear evidence of cointegration for all countries except Germany. Our finding implies that, especially in the case of UK, we may achieve important implications by taking account of possible nonlinearities. Overall, our findings support the proposition of expectation hypothesis for all of the G7 countries except Germany.